0
$\begingroup$

Minimize $$(p \land q) \lor (\neg p \lor q)$$ without using a truth table.

I have tried with an online website and it shows $\neg p \lor q$ as the answer. I was able to verify with truth table but I don't get how to approach it.

PS: I have a basic idea of the idempotent associative laws, etc and I am new to discrete mathematics.

$\endgroup$
3
$\begingroup$

$(p\wedge q)\vee(\neg p\vee q)=(\underbrace{p\vee \neg p}_{1} \vee q)\wedge(q\vee\neg p \vee q)=1\wedge (q\vee \neg p)=\neg p\vee q$

just like J.G. said.

$\endgroup$
0
$\begingroup$

Conjunction elimination $$(p\land q)\to(p\to q)$$ Disjunction elimination $$(-p\lor q)\to (-p\to -q)$$ Disjunction introduction $$(-p\to -q)\lor(p\to q)\to (-p\lor q) \boldsymbol{\text{or}} (p\lor -q)$$

We'll pick the first for sanity.

$\endgroup$
0
$\begingroup$

If $p\land q$, then $q$ and in particular $\neg p\lor q$. So $(p\land q)\lor(\neg p\lor q)$ is just $\neg p\lor q$.

$\endgroup$
0
$\begingroup$

Translating to Boolean algebra,

$$pq + \bar{p} + q = \underbrace{(p+1)}_{=1} q + \bar{p} = q + \bar{p} = \bar{p} + q$$

$\endgroup$
0
$\begingroup$

$$(p \land q) \lor (\neg p \lor q)\\ =(p\lor\neg p\lor q)\land(q\lor\neg p\lor q)\\ =T\land(\neg p\lor q)\\ =\neg p \lor q$$

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.